2011
DOI: 10.1148/radiol.11110542
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative CT Assessment of Emphysema and Airways in Relation to Lung Cancer Risk

Abstract: Purpose:To determine whether quantitative computed tomographic (CT) measurements of emphysema and airway dimensions are associated with lung cancer risk in a screening population. Materials and Methods:Institutional review board approval and informed consent for the use of deidentifi ed images were obtained. In this retrospective study, CT scans were analyzed from 279 participants in the CT screening arm of the National Lung Screening Trial who were diagnosed with lung cancer and 279 participants who were not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 35 publications
2
43
1
Order By: Relevance
“…Although associated with an increased risk of lung cancer in some studies, the overall role of emphysema as a risk factor for lung cancer is still under investigation (22)(23)(24)(25)(26)(27)(28)(29). However, risk factors for incident lung cancer and those related to prognosis are not necessarily the same (e.g., radon exposure).…”
Section: Original Researchmentioning
confidence: 99%
“…Although associated with an increased risk of lung cancer in some studies, the overall role of emphysema as a risk factor for lung cancer is still under investigation (22)(23)(24)(25)(26)(27)(28)(29). However, risk factors for incident lung cancer and those related to prognosis are not necessarily the same (e.g., radon exposure).…”
Section: Original Researchmentioning
confidence: 99%
“…By contrast, MALDONADO et al [24] reported that the radiographic evidence for emphysema, evaluated by automated quantitative computed tomography analysis, was not a significant risk for lung cancer (OR 1.042, 95% CI 0.816-1.329) and emphysema severity was also not associated with lung cancer (OR 1.57, 95% CI 0. 73-3.37 [26] reported that not only emphysema but also bronchial measurements at segmental-subsegmental levels, as assessed by automated computed tomography analysis, were not also associated with lung cancer. WILSON et al [27] reported that their casecontrol study of 117 lung cancer cases did not reveal any evidence that either airway obstruction or emphysema, as assessed by quantitative analysis of computed tomography images, was associated with increased risk of lung cancer.…”
Section: Epidemiology and Risk Of Lung Cancer In Copd Patientsmentioning
confidence: 99%
“…Conversely, no association between emphysema features as assessed by automated CT analysis and lung cancer was observed.Our findings are not only in keeping with previous studies reporting no association between whole-lung emphysema extent as quantified by automated CT analysis and lung cancer, but also expand on this by including a number of cases recruited outside the screening context. 2,[8][9][10] The inclusion of such cases provides a more representative picture of the disease, owing to the inclusion of a higher proportion of tumours at advanced stages. Nevertheless, the lack of association between whole-lung emphysema extent and lung cancer was maintained for both screening and non-screening detected cases.…”
Section: Discussionmentioning
confidence: 99%
“…2,[8][9][10] In addition, two studies recently reported no association between automated CT measures of proximal (segmental and subsegmental) airway disease and lung cancer. 9,10 However, previous studies did only include subjects with lung cancer detected in a screening setting and the emphysema phenotype as well as MLD were not fully assessed. 2,5,6,[8][9][10] There is evidence that screening-detected lung cancers may differ from the general pool of lung cancers in their morphology, histology, and prognosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation